Influence of cervical spinal cord injury on thermoregulatory and cardiovascular responses in the human body: Literature review. (November 2019) - Mneimneh, Farah; Moussalem, Charbel; Ghaddar, Nesreen; Aboughali, Kamel; Omeis, Ibrahim
Highlights: Cervical spinal cord injury is a major public health problem. Pathophysiology after spinal cord injury is not well understood. Spinal cord injury is characterized by a change in cardiac output & thermoregulation. Understanding the pathophysiology after cervical spinal cord injury is crucial. This might provide insights to treat patients, providing a better quality of life. Abstract: Background: Cervical spinal cord injury (cSCI) is a major public health concern in the young population as per the estimation of the annual global report, which concluded that the amount of incidence in this area ranged between 11.5 and 53.4 cases per million population. Moreover, Despite the many evaluations conducted to unveil the physiological and thermo logical complications caused to the human body after a cervical spinal cord injury, the fundamental pathophysiology about this type of injury is still inconclusive. Objective: This review attempts to provide a better understanding to the various changes caused to the body after a cSCI. It focuses on the alterations in blood circulation, energy expenditure (EE), sweating, shivering responses and consequently disruption in body temperature regulation. Methods: Various research engines such as Scopus, PubMed, Embase, Web of Science, EBSCO, and Cochrane Library databases were searched by two independent investigators. 17 studies out of 102 were included based on eligibility criteria: patients with complete and/or incomplete cSCI; minimum of 5 patients as participants; and control group of able Bodied People (AB). Results: Following cSCI, EE decreases by 10% ( p < 0.05) due to reduction in lean body mass; cardiac output decrements by 27% ( p < 0.05) following the change in arterial blood vessel structure, and finally; thermoregulatory responses were disturbed because of the absence or decrease in vasodilation, vasoconstriction, sudomotor (autonomic activation of sweat glands) and shivering responses. Conclusions: The body undergoes significant thermoregulatory changes following spinal cord injury. Understanding the pathophysiology of spinal cord injury and its effect on the human body can provide us an insight to develop adequate treatment modalities that tackle the problem of thermal dysregulation in people with cSCI.